STEAM-Based Science Student Worksheets to Improve Elementary School Students' Scientific Literacy - Afrijal; Yulianti, Dwi; Rohman, Fatkhur; Sunyono (Thinking Skills and Creativity Journal, 2023)
This research was motivated by students' low scientific literacy skills and learning that only used textbooks. It is hoped that STEAM-based student worksheets can be an alternative to improving students' scientific literacy skills. This research aims to analyze student worksheets that are valid, practical, and effective for enhancing students' scientific literacy skills. Research and development (R&D) research on the ADDIE (Analyze, Design, Develop, Implementation, Evaluation) development model. The research subjects were determined by simple random sampling of 62 fifth-grade elementary school students and 2 class teachers. Data was collected using valid and reliable interviews, questionnaires, and tested methods. Product validation test results show that Aiken's overall validity index is 0.802, which belongs to the very effective category. Valid STEAM-based student worksheets that integrate various scientific disciplines, namely science, technology, engineering, art, and mathematics, contextually in one complete learning approach. Practicality is measured through STEAM-based learning, with an average implementation value of 4.91 teacher responses and 4.88 student responses in the practical category, implying that all learning activities can be completed effectively within the allotted time. The paired t-test for scientific literacy achievement produced a significance value of 0.020 < 0.05 with Sig. t-tail, meaning Ho is rejected. Based on the research results, the STEAM-based science worksheet developed is valid, practical, and effective in improving the scientific literacy skills of elementary school students.